Improving photocurrent generation: Supramolecularly and covalently functionalized single-wall carbon nanotubes-polymer/porphyrin donor-acceptor nanohybrids - Rahman, Aminur; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Jux, Norbert; Tchoul, Maxim N.; Ford, Warren T.; Mateo-Alonso, Aurelio; Prato, Maurizio (Chemistry - A European Journal, 2008)
Novel nanohybrids based on covalently and noncovalently functionalized single-wall carbon nanotubes (SWNTs) have been prepared and assembled for the construction of photoactive electrodes. Polymer-grafted SWNTs were synthesized by free-radical polymerization of (vinylbenzyl)trimethylammonium chloride. Poly[(vinylbenzyl)trimethylammonium chloride] (PVBTA) was also noncovalently wrapped around SWNTs to form stable, positively charged SWNT/PVBTA suspensions in water. Versatile donor-acceptor nanohybrids were prepared by using the electrostatic/van der Waals interactions between covalent SWNT-PVBTA and/or noncovalent SWNT/PVBTA and porphyrins (HP and/or ZnP ). Several spectroscopic, microscopic, transient, and photoelectrochemical measurements were taken to characterize the resulting supramolecular complexes. Photoexcitation of the nanohybrids afforded long-lived radical ion pairs with lifetimes as long as 2.2 us. In the final part, photoactive electrodes were constructed by using a layer-by-layer technique on an indium tin oxide covered glass support. Photocurrent measurements gave remarkable internal photon-to-current efficiencies of 3.81 and 9.90% for the covalent ZnP-/SWNT-PVBTA and noncovalent ZnP /SWNT/PVBTA complex, respectively, when a potential of 0.5 V was applied. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.